Reflections: complex thought and the principle of feedback in education (Revista Electrónica REDINE, 2018)
The following essay is based upon reflections about possible applications of principles of complex thought in education. Thus, the content of the  article  highlights present inconvenient as to how to reach and spread the importance and praxis of the principles of complexity in education nowadays. Facing this reality, some question arise: in what way can the complex thought be thrusted during the teaching – learning process in classrooms? What principle of complexity must initially be brought  upon education? Can  the feedback principle be fundamental in the educational  formation of the  social  actor?  Due to such reasons, during the extension of the essay, a  couple  of introspections will emerge and they will try to answer the afore mentioned questions with the purpose of elevating the interest of every party involved in the educational field about the topic portrayed.
Keywords: complex thought; education; feedback process